PENGARUH PROFESIONALISME DALAM MENINGKATKAN KINERJA AUDITOR INTERNAL (STUDI PADA INSPEKTORAT PROVINSI SULAWESI TENGGARA) - Dalli, Nasrullah; Ariyanti, Jully (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACTÂ The aims of the study was to examine the effect of profesionalism to internalÂ  auditors performance. The primary data in this study was obtained from the all auditors perception at the inspectorate of south east sulawesi province. Respondents perceptions measured by the answer of questionnaires used ordinal measurement woth 5 likert scale. The statistical method used to test hypotesis was simple linear regression analysis.The result of the study showed that profesionalism gave significant effect toward internal auditors performance. Coefficient adjust R Square of regression is 0,793. This study showed that various of ability shown the free variable, namely : profesionalism toward independent variable, the internal auditors performance is 79,3%. While the rest is 20,7% explained by other variables.Keywords:Â  Profesionalism,Â  internal auditorâs performance.